Women in Water Utilities : Breaking Barriers - World Bank (World Bank, Washington, DC, 2019)
Women are significantly underrepresented in the water workforce. Multiple barriers, ranging from social norms, to inadequate HR policies, to an unwelcoming work environment, pose challenges to female water professionals’ entering, staying and advancing in the water sector. This study explores these barriers and provides utilities with practical approaches to advance their gender diversity.